Analsis Wacana Berita Pemilu Presiden 2014 (Studi pada 10 Portal Berita Terbaik Tahun 2013) - Bambang Hariyanto (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
Online media as one of the information for many people today, it is also as the important part of every aspects of the human life especially in politics. Party of democracy in the election on July 9, 2014 gave us the unforgetable question in our mind how the candidate able to be recognized by the voters trough the online media information. This article explores to the readers that the language has a power to persuade, to create opinion, invite or even influence the readers to follow what the writer wants. In the election of presidential last time, many wars happen in the form of words and argumentations in portal media. The result shows that there are several  forms of invitation which is often used by the candidates to invite or influence the voters to support and give their vote in the election day. It is used by the candidate to upgrade their electability trough online media.